2023
DOI: 10.47191/jefms/v6-i5-10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transformational Leadership Style on Organizational Commitment, Employee Engagement, and Employee Performance at Pt. Pln (Persero) Up3 Bukittinggi

Abstract: This study aims to analyze the effect of Transformational Leadership Style on Organizational Commitment, Employee Engagement, and Employee Performance at PT. PLN (Persero) UP3 Bukittinggi. This type of research is quantitative research. The population is in the form of employees of PT. PLN (Persero) UP3 Bukittinggi with 53 employees. The characteristics used are employees of PT. PLN (Persero) UP3 Bukittinggi (Non Managerial) who is a permanent employee and has worked for at least 1 year at the company, assumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The activities of the leader may ensure that the goal is reached. There are seven distinct philosophies of leadership: Research by Aesah et al (2023) ; Aferi et al (2023), revealed that leaders often modify their approach according to the environment and organizational structure. Leadership philosophy may change in response to social dynamics or organizational environment.…”
Section: Kind Of Leadershipmentioning
confidence: 99%
“…The activities of the leader may ensure that the goal is reached. There are seven distinct philosophies of leadership: Research by Aesah et al (2023) ; Aferi et al (2023), revealed that leaders often modify their approach according to the environment and organizational structure. Leadership philosophy may change in response to social dynamics or organizational environment.…”
Section: Kind Of Leadershipmentioning
confidence: 99%